Clinicopathological and Preclinical Patient-Derived Model Studies Define High Expression of NRN1 as a Diagnostic and Therapeutic Target for Clear Cell Renal Cell Carcinoma - Kamada, Shuhei; Ikeda, Kazuhiro; Suzuki, Takashi; Sato, Wataru; Kitayama, Sachi; Kawakami, Satoru; Ichikawa, Tomohiko; Horie, Kuniko; Inoue, Satoshi (Frontiers in Oncology, 2021)
Background Acquired therapeutic resistance and metastasis/recurrence remain significant challenge in advance renal cell carcinoma (RCC), thus the establishment of patient-derived cancer models may provide a clue to assess the problem. We recently characterized that neuritogenesis-related protein neuritin 1 (NRN1) functions as an oncogene in testicular germ cell tumor. This study aims to elucidate the role of NRN1 in RCC. Methods NRN1 expression in clinical RCC specimens was analyzed based on immunohistochemistry. NRN1-associated genes in RCC were screened by the RNA-sequencing dataset from The Cancer Genome Atlas (TCGA). RCC patient-derived cancer cell (RCC-PDC) spheroid cultures were established and their viabilities were evaluated under the condition of gene silencing/overexpression. The therapeutic effect of NRN1-specific siRNA was evaluated in RCC-PDC xenograft models. Results NRN1 immunoreactivity was positively associated with shorter overall survival in RCC patients. In TCGA RCC RNA-sequencing dataset, C-X-C chemokine receptor type 4 (CXCR4), a prognostic and stemness-related factor in RCC, is a gene whose expression is substantially correlated with NRN1 expression. Gain- and loss-of-function studies in RCC-PDC spheroid cultures revealed that NRN1 significantly promotes cell viability along with the upregulation of CXCR4. The NRN1-specific siRNA injection significantly suppressed the proliferation of RCC-PDC-derived xenograft tumors, in which CXCR4 expression is significantly repressed. Conclusion NRN1 can be a potential diagnostic and therapeutic target in RCC as analyzed by preclinical patient-derived cancer models and clinicopathological studies.